A CONTRASTIVE ANALYSIS OF ARABIC AND ENGLISH NOUN PLURAL MARKERS - Aliyatul Himmah; Ribut Wahyudi (Master Program in Linguistics, Diponegoro University, 2014)
This paper is attempting to explore the plural markers in both Arabic and English. The data collected qualitatively are sorted to meet the scope of this paper. Through contrastive analysis, it is discovered that there are numerous significant differences rather than similarities in terms of syllable count start, patterns of plural nouns in relation to gender, regularity, regular vs irregular plural and internal vowel change. Moreover, Arabic has some uniqueness in its plural marking system. Being well informed on all of these might pave the way for second or foreign language learners to comprehensively understand the plural marking system in Arabic and English. Tulisan ini mencoba untuk mengeksplorasi penanda jamak dalam bahasa Arab dan bahasa Inggris. Data yang dikumpulkan secara kualitatif diurutkan untuk memenuhi cakupan makalah ini. Melalui analisis kontrastif, ditemukan banyak perbedaan yang signifikan daripada kesamaan dalam segi jumlah awal suku kata, pola kata benda jamak dalam kaitannya dengan gender, keteraturan dan ketidakteraturan jamak, serta perubahan vokal. Selain itu, bahasa Arab memiliki beberapa keunikan dalam sistem menandai jamaknya. Memahami informasi hal tersebut dengan baik mungkin memudahkan pembelajar bahasa kedua atau asing untuk memahami secara komprehensif sistem penanda jamak dalam bahasa Arab dan Inggris